Gendered media : women, men, and identity politics - Ross, Karen, 1957- (Critical media studies., 2010)
Gendered Media addresses the broad topic of gender and media, where 'gender' is not simply a shorthand for 'woman' but also embraces masculinitiy/ies, queer, lesbian and gay identities. Karen Ross provides the necessary historical context against which to read recent sex- and gender-based media phenomena such as Big Brother, Terminator, girls' use of mobile phones, women news editors, the Wonderbra generation, the Hillary Clinton and Sarah Palin phenomena, and so on. The book is an overview of the various aspects of gender and media in one volume. The book provides introductory overviews to th.